(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2022)
With the method of variational pulsometry by R.M.Baevsky, the influence of classical music on the integral and spectral characteristics of the activity of the regulatory mechanisms of the heart rhythm of students, observed during a one-day study load, was studied by the method of computer registration and analysis of the ECG. ECG registration and analysis were carried out on students of Yerevan State University in three experimental situations: before the first lesson (physiological norm); after the end of the 6th lesson; after listening to classical music for 20 min. Two types of response of the functional indicators of students to the study load were revealed: sympathetic and parasympathetic. It has been established that after a study load, a session of music therapy contributes to a return of the levels of all studied heart rate indicators towards the physiological norm (initial values before the class).